2022
DOI: 10.1002/ccr3.5714
|View full text |Cite
|
Sign up to set email alerts
|

Nonocclusive mesenteric ischemia during treatment for ketoacidosis associated with acute‐onset type 1 diabetes mellitus: A case report

Abstract: This case report describes a patient with nonocclusive mesenteric ischemia that developed due to diabetic ketoacidosis. We believe that early diagnosis and intervention may improve the prognosis of nonocclusive mesenteric ischemia that has low vascular risk, with the major risk factor being dehydration due to diabetic ketoacidosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…12 It has been reported that the mortality rate with delayed interventions can be up to 90%. 18,19 In our case, the patient had multiple episodes of DKA due to poor compliance with diabetes treatment due to poor socioeconomic background. He survived following two bowel resection surgeries, but the treatment was futile on the last presentation due to extensive bowel necrosis and frozen abdomen due to dense adhesions from the previous surgeries in the abdomen.…”
Section: Discussionmentioning
confidence: 74%
“…12 It has been reported that the mortality rate with delayed interventions can be up to 90%. 18,19 In our case, the patient had multiple episodes of DKA due to poor compliance with diabetes treatment due to poor socioeconomic background. He survived following two bowel resection surgeries, but the treatment was futile on the last presentation due to extensive bowel necrosis and frozen abdomen due to dense adhesions from the previous surgeries in the abdomen.…”
Section: Discussionmentioning
confidence: 74%